PENGARUH EDUKASI MENGGUNAKAN MEDIA LEAFLET TERHADAP PERUBAHAN TINGKAT PENGETAHUAN TENTANG PENTINGNYA SADARI PADA REMAJA PUTRI DI SMPN 2 PASAR KEMIS - zakiyatun nupus nupus (Jurnal Riset Media Keperawatan, 2026)
Breast cancer or tumors are a serious health problem with global impact, including in indonesia. Early detection of breast cancer self- examination (BSE) has been carried out, mainly by Ismaia Putri. However, many still lack adequate knowledge about BSE. Using quantitative research with a pre-experimental approach and using a singel-group approach. The study used a non-probability sampling of 52 respondents. The analysis results showed that the Asymptotic value, Sig(2-tailed) was obtained at 0.000, with a Sig value of 0,000<0,05. This shows that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. There is an influence of education through media (leaflet) on the level of knowledge off female adolescents regarding the importance of breast self-examination at SMP Negeri 2 Pasar Kemis Keywords: Level of Knowledge, Breast Self-Examination (SADARI)